Hierarchically aligned fibrin nanofiber hydrogel accelerated axonal regrowth and locomotor function recovery in rat spinal cord injury - Yao, Shenglian (Int J Nanomedicine, 2018)
BACKGROUND: Designing novel biomaterials that incorporate or mimic the functions of extracellular matrix to deliver precise regulatory signals for tissue regeneration is the focus of current intensive research efforts in tissue engineering and regenerative medicine. METHODS AND RESULTS: To mimic the natural environment of the spinal cord tissue, a three-dimensional hierarchically aligned fibrin hydrogel (AFG) with oriented topography and soft stiffness has been fabricated by electrospinning and a concurrent molecular self-assembling process. In this study, the AFG was implanted into a rat dorsal hemisected spinal cord injury model to bridge the lesion site. Host cells invaded promptly along the aligned fibrin hydrogels to form aligned tissue cables in the first week, and then were followed by axonal regrowth. At 4 weeks after the surgery, neurofilament (NF)-positive staining fibers were detected near the rostral end as well as the middle site of defect, which aligned along the tissue cables. Abundant NF- and GAP-43-positive staining indicated new axon regrowth in the oriented tissue cables, which penetrated throughout the lesion site in 8 weeks. Additionally, the abundant blood vessels marked with RECA-1 had reconstructed within the lesion site at 4 weeks after surgery. Basso-Beattie-Bresnahan scoring showed that the locomotor performance of the AFG group recovered much faster than that of blank control group or the random fibrin hydrogel (RFG) group from 2 weeks after surgery. Furthermore, diffusion tensor imaging tractography of MRI confirmed the optimal axon fiber reconstruction compared with the RFG and control groups. CONCLUSION: Taken together, our results suggested that the AFG scaffold provided an inductive matrix for accelerating directional host cell invasion, vascular system reconstruction, and axonal regrowth, which could promote and support extensive aligned axonal regrowth and locomotor function recovery.